PEMBATALAN KHITBAH DAN PENGEMBALIAN HANTARAN KHITBAH MENURUT HUKUM ISLAM (STUDI KASUS DI KECAMATAN BOJONG KABUPATEN PEKALONGAN) - hesti silfiani (Al-Hukkam: Journal of Islamic Family Law, 2022)
Sermons are bound by the consequences of promises by both that must be kept. However, not all of those who do sermons reach marriage, as in Bojong District, Pekalongan Regency, the cancellation of the sermon considers that the best way for couples who have held a sermon with the problems they face. This choice does not make the right solution to the problem but creates new problems after the sermon is canceled. This also relates to the goods given by the men when the khitbah is canceled. This problem is not a trivial thing to be played with. There are various reasons for the cancellation of the sermon from each party, it seems that they are playing games, not applying the value of the sermon, namely heading to the marriage level. This research is a field research, using a normative approach that is based on Islamic law and is descriptive qualitative. This research is based on primary and secondary data collected in interview, observation and documentation studies. This study explores the causes of the cancellation of the sermon and the return of the delivery of the sermon that occurred in the District of Bojong, Pekalongan Regency and analyzed them from the perspective of Islamic law. The phenomenon of the cancellation of the sermon and the return of the delivery of the sermon that occurred in Bojong District, Pekalongan Regency, was caused by differences in weton, no compatibility and the presence of a third party. Regarding the delivery of the sermon, there are also parties who take the initiative to return it and are asked to return it.